The INFLUENCE OF WORK COMPETENCY, WORKLOAD, AND JOB TRAINING ON THE WORK ACTIVITY OF LAZADA LOGISTICS COURIER - Nathiqah; Pancasasti, Ranthy (PT Larva Wijaya Penerbit, 2022)
This study was conducted to determine the effect of Competence (X1), Workload (X2), and On The Job Training (X3) on Work Productivity (Y) at Lazada Logistics Hub Leu Serang. In this research, the method used is quantitative research. The population in this study were 155 Lazada Logistics Hub Leu Serang couriers with a total sample of 85 respondents. The sampling technique in this study is simple random sampling, which is random and simple sampling without regard to the level (strata) contained in the population. The method of collecting data in this study is using a questionnaire and analyzing the data using Structural Equation Modeling (SEM) with the student version of Smart Partial Least Square (Smart-PLS) 3.3.2 software. The research results obtained are: First, competence has a positive and significant effect on work productivity. the t-statistic value is 3.399 > 1.96 with a large effect of 0.399 and a P-value of 0.001 < 0.05. Second, workload has a positive and significant effect on work productivity and has the most dominant influence on work productivity. the t-statistic value is 3.924 > 1.96 with a large effect of 0.415 and a P-value of 0.000 <0.05. Third, on the job training has a positive and significant effect on work productivity. the t-statistic value is 2.399 > 1.96 with a large influence of 0.180 and a P-value of 0.017 < 0.05.